Interest Rate Uncertainty and Stock Market Volatility - XU, Jincai (Institutional Knowledge at Singapore Management University, 2007)
The reason for volatility changing over time is still open. As stated in the extant papers uncertainty of Macroeconomic variable plays more important role in explaining the time varying of volatility than the volatility of Macroeconomic variable itself. In this paper we illustrate this with exploring the relationship between stock market volatility and the Interest Uncertainty. In the paper, we take the uncertainty of the decision of FOMC meeting as the uncertainty of interest rate. As we know, asset price is a tool for people to express their belief about the state of the economy, when uncertainty is high, a slight change in the belief will cause substantial shift in their holdings. Thus we expect that stock market volatility is increasing with uncertainty of interest rate. By using the Federal Fund Future to measure the uncertainty, we find the significance of impact of uncertainty on volatility is different across industries. In addition, the relationship between interest uncertainty and stock volatility is stronger for small firms than that for big firms. In addition, we investigate the possible reason for the sensitivity of interest rate uncertainty, the empirical results confirm that dividend yield is the factor that impacted most, comparing to the leverage ratio which represent the capital structure is not an important factor.